Residential parenting services: An integrative literature review of characteristics, service usage and parent and staff perspectives - Hannah Grace Dahlen; Simone Maree Ormsby; Suzanne Brownhill; Cathrine Fowler; Virginia Schmied (Wiley, 2023)
Abstract Aims The primary aim of the review was to provide an overall assessment of residential parenting services in Australia, by describing the characteristics of infants and parents using residential parenting services, their prior service use and reasons for admission, referral pathways for access and parenting and infant outcomes. The secondary aims were to explore parent and staff perception of the programmes. Design An integrative literature review. Methods A systematic and comprehensive search of health and social sciences databases was conducted for studies related to residential parenting services (published between 1st January 1990-31st December 2019). Six hundred and eleven peer‐reviewed papers were identified, after which 301 duplicates were removed and an additional 256 papers excluded after titles/abstracts were read. Of the remaining 54 abstracts/papers, a further 14 were omitted as not relevant. Forty papers were independently reviewed by four authors. ENTREQ and MOOSE checklists were applied. Results Thirty studies were quantitative, nine were qualitative, and one was mixed methods. All studies originated from in Australia. Women and babies admitted to residential parenting services were found more likely to be: older, Australian born, from higher socio‐economic groups, and first‐time mothers, and having labour and birth interventions and a history of mental health disorders. The babies were more likely to be twins, male and admitted with sleep disorders and dysregulated behaviour. Studies reporting postintervention outcomes demonstrated improvements to maternal mental health, breastfeeding, parenting confidence and sleep quality, and infant sleeping and behaviour.